OPTIMALISASI PENULISAN KARYA ILMIAH PADA ERA DIGITAL BAGI SISWA - Nasrodin Nasrodin; Riza Faishol; Muhammad Royyan; Rini Dewi Safitri (LPPM Institut Agama Islam (IAI) Ibrahimy Genteng Banyuwangi, 2024)
Limitations in writing skills can arise because of the difficulty of mastering these language skills compared to language skills. This devotion aims to provide knowledge and skills in writing scientific articles of papers. The approach used in dedication to writing this scientific paper is Service Learning (SL). This service is carried out through the stages of providing a number of materials on how and tricks to write papers, providing opportunities for each participant in practical training in each session and reflecting, and guiding participants to complete papers. While the results of this dedication students have knowledge and understanding of preparing papers, the ability to compile papers, and have the ability to access various references from various sources. The result of this activity is that students are able to write papers properly and correctly and apply them in the academic world.